MiR-486-5p Serves as a Good Biomarker in Nonsmall Cell Lung Cancer and Suppresses Cell Growth With the Involvement of a Target PIK3R1 - Tian, Fei; Wang, Jun; Ouyang, Tinglan; Lu, Na; Lu, Jiafeng; Shen, Yanting; Bai, Yunfei; Xie, Xueying; Ge, Qinyu (Frontiers in Genetics, 2019)
MicroRNAs are a class of non-coding RNAs that can be involved in the regulation of gene expression in cancers, including lung cancer. Our previous research has shown that miR-486-5p is one of the most down-regulated microRNAs in tissue and serum samples of lung cancer as a good diagnostic biomarker. The objective of this study is to investigate the roles of miR-486-5p in the progression of lung cancer. In this study, miR-486-5p was further validated to be significantly down-regulated in additional NSCLC tissue, serum and cell samples by quantitative RT-PCR, and the expression level of miR-486-5p was significantly associated with clinical phenotype of NSCLC. The PIK3R1 gene was confirmed to be a direct target of miR-486-5p by dual-luciferase reporter assay, and the expression level of miR-486-5p was inversely correlated with that of PIK3R1 in tumor tissues (r = -0.774, p < 0.01). Over-expressed miR-486-5p effectively inhibited cell proliferation and invasion, and successfully induced apoptosis in vitro. PIK3R1 was involved in the suppression of miR-486-5p on cell growth. It can be concluded that miR-486-5p may act as a tumor-suppressor contributing to the progression of NSCLC, and miR-486-5p would be a diagnostic and prognostic biomarker, and a potential therapeutic target for lung cancer.